Effects of Adenosine Diphosphate, Colchicine and Temperature on Size of Human Platelets - Laufer, N; Grover, N B; Ben-Sasson, S; Freund, H (Thrombosis and Haemostasis, 1979)
An improved measuring system based on the Coulter principle and developed in our laboratory is used to size human blood platelets.The mean volume of platelets in 24 healthy subjects is found to be 8.45 μm3 with a standard deviation of 1.07 μm3; the typical size-distribution curve is unimodal and asymmetrical, with a marked skew to the right.The effects of different reagents on platelet size (shape factor × volume) are evaluated. Platelets increase in size by 23% following suspension in isotonic, phosphate-buffered saline and incubation with 10 μM adenosine diphosphate; no change is observed when the suspending medium is autologous plasma. Cooling the platelets to 0-4° C results in a size increase of 25%; rewarming to 37° C restores them to their initial size within 2 hr. A similar increase occurs when the platelets are incubated with 1-10 mM colchicine.It is proposed that these reagents, which are known to produce changes in the orientation of the marginal bundle of microtubules, cause platelets to undergo disc-sphere transformations.Calculations are made which show that such transformations increase platelet size by 27% as measured electrically, and we conclude that the so-called volume changes reported in the literature reflect shape changes only and that no true volume increase actually takes place.